Castration and emasculation in the Middle Age. The andrological conundrum of Peter Abelard. (13th April 2022) - Sansone, Andrea; Jannini, Tommaso B.; Dolci, Susanna; Jannini, Emmanuele A.
Abstract: Peter Abelard (1079–1142) is still considered one of the giants of philosophy, theology, and psychology, and the unsurpassed master of dialectical debate. Born in Le Pallet, near Nantes, Abelard became an academic and wandering cleric of great fame, founder of several schools that attracted students from all countries, arousing the admiration of his contemporaries and the profound envy of his colleagues. Around 1115, Abelard became master of the school of the Cathedral of Notre‐Dame. Shortly after, the canon Fulbert asked him to take his niece, the equally famous and highly cultured Héloïse d'Argenteuil (1092–1164), as a pupil. Thus a relationship began, celebrated for centuries to come, characterized by burning sexual and intellectual passion, by the famous correspondence, which will be the archetype of sentimental education and the template of romantic love letters, bythe birth of a son and consequent marriage, and by the cowardly revenge of Fulbert, who, together with a band of servants, mutilated "those parts of my body with which I had done what was the cause of their pain, " as Abelard wrote. While this unclear self‐description has suggested to contemporaries and to posterity that Abelard was castrated, we aim to question this belief by analyzing in‐depth this historical‐andrological clinical case to understand if there is any evidence that could suggest that Abelard was instead the victim of an even more brutal punishment: penectomy. Signs and symptoms gleaned from the personal writings and historical perspectives of Abelard and his time are used here to provide a possible answer to a thousand‐year‐old question: what makes a man … a man?